Implementasi Teknologi Flaudized Bed Cover (FBD) dan Perencanaan Human Capital untuk Peningkatan Kualitas Garam Indonesia di PT. Ladang Garam Indonesia - Muhammad Iqbal Ramadhan; Tantri Yanuar Rahmat Syah; Dimas Angga Negoro; Endang Ruswanti (Yayasan Literasi Sains Indonesia, 2025)
PT Ladang Garam Nasional (PT LGN) aims to be a pioneer in the caustic soda salt industry in Indonesia by utilizing modern technology to meet the needs of the national chemical industry. This project is driven by Indonesia's dependence on industrial salt imports, especially for the chemical sector, which reaches more than 3 million tons per year. With the establishment of a factory in Tegal, Central Java, PT LGN will produce high-quality salt with a NaCl content of ≥99% through Fluidized Bed Dryer (FBD) technology and apply the principles of Good Manufacturing Practice (GMP). The global industrial salt market is projected to grow by 2.4% per year. PT LGN takes advantage of this opportunity by offering products that meet the specific needs of the caustic soda industry. This project will also support the government's program for salt self-sufficiency, create jobs, and reduce imports. The method used in this study is a qualitative approach with case studies on several industrial salt processing companies that have adopted advanced technology. The results of the study indicate that mature internal planning, including supply chain management, production management, and quality control, is very important in increasing the competitiveness of the salt industry. This study provides recommendations for salt processing companies to maximize the potential of technology in supporting business planning and HR management, as well as increasing global market competitiveness.